2017
DOI: 10.18632/oncotarget.18082
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI3K/AKT/mTOR pathway activates autophagy and compensatory Ras/Raf/MEK/ERK signalling in prostate cancer

Abstract: The PI3K/AKT/mTOR pathway is frequently activated in advanced prostate cancer, due to loss of the tumour suppressor PTEN, and is an important axis for drug development. We have assessed the molecular and functional consequences of pathway blockade by inhibiting AKT and mTOR kinases either in combination or as individual drug treatments. In established prostate cancer cell lines, a decrease in cell viability and in phospho-biomarker expression was observed. Although apoptosis was not induced, a G1 growth arrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 67 publications
3
73
0
1
Order By: Relevance
“…In addition, using a panel of cell lines may also not be a great improvement because results from experiments in cell lines have been seen here and in other studies to be quite different from primary cells [26][27][28] . Cells in primary cultures have compensatory signaling pathways that have been lost in cell lines, and so an inhibitor that works well in cell lines may be less effective or ineffective in primary cultures [28] . This is one explanation for such high attrition rate in the drug pipeline; weak, incomplete, unrepresentative or inappropriate models.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, using a panel of cell lines may also not be a great improvement because results from experiments in cell lines have been seen here and in other studies to be quite different from primary cells [26][27][28] . Cells in primary cultures have compensatory signaling pathways that have been lost in cell lines, and so an inhibitor that works well in cell lines may be less effective or ineffective in primary cultures [28] . This is one explanation for such high attrition rate in the drug pipeline; weak, incomplete, unrepresentative or inappropriate models.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, we found that TSPY1 contributed to the upregulation of p‐RAF1, p‐MEK1/2, and p‐ERK1/2 in the RAS signaling pathway in both A549 and HepG2 cells and that the JUN protein level was consequently increased (Figures B and ). Considering the significance of PI3K/AKT/mTOR/BCL2 and RAS/RAF/MEK/ERK/JUN signaling pathways in cell proliferation, cycle, invasiveness, and apoptosis, we propose that TSPY1 affects cell biological phenotypes probably through a cross‐talk network that involves the molecules with functional regulation of both PI3K/AKT and RAS signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…C, Western blot analysis showed higher levels of 4 key proteins (p-RAF-1, p-MEK1/2, p-ERK1/2, and JUN) of the RAS signaling pathway in A549 and HepG2 cells with IGFBP3 knockdown, relative to controls (shNC and siNC) signaling pathways, and this promotion depended on the inhibition of TSPY1 on IGFBP3 expression. The PI3K/AKT and RAS signaling pathways are key signal transduction components in the regulation of cell growth, cell differentiation, cell cycle, apoptosis, and metastasis, [22][23][24][25][26] and recent reports show that deregulated activation of the 2 signalings is frequently observed in many cancers. [29][30][31] Therefore, our findings provided a potential common mechanism of TSPY1's function as an oncogene in the tumor process.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR functions at the center of various signaling pathways, and the classic PI3K/Akt/mTOR pathway regulates autophagy mainly through the activation of mTOR [34]. PtdIns(3, 4)P2 and PtdIns(3, 4,5) P3, produced by class I PI3K, can interact with the pleckstrin homology domain of Akt, activating the Akt signaling pathway, which indirectly activates mTOR to inhibit autophagy [35].…”
Section: Resultsmentioning
confidence: 99%